Zagadnienie istoty szczęścia i sposobu jego osiągnięcia w traktacie "O życiu szczęśliwym" Seneki Młodszego - Picewicz, Joanna (Teologia i Moralność, 2018)
The paper discusses the question of happiness according to the treatise “On the Happy Life” by Seneca the Younger. The world-cosmos, thus all that surrounds us, is of rational and divine character. All that exists and happens in the universe is due to necessity, some form of fate. The meaning and goal of human existence is a happy life, in harmony with nature, i.e. divine Logos, immersed in the universe. For Seneca, to live in harmony with nature means to live in harmony with Logos, his rational laws, and principles.